Physico-chemical Properties, biological activities and authentication of cod liver oil - Rohman, Abdul (Fakultas Farmasi, Universitas Gadjah Mada, 2017)
Cod liver oil (CLO), currently, has attracted public awareness and researchers as functional food oils. It is predicted that CLO will experience a great market in the fats and oils industry. CLO has been known to have several biological activities and its price is much higher (10–15 times) than common edible oils, thus CLO is subjected to adulteration with lower priced oils, therefore its authentication is highlighted in this review. This article highlighted some of the reported activities of CLO like the prevention of coronary heart disease. In addition, physico-chemical properties of CLO were also described in this review. Some analytical methods, especially spectroscopy and chromatographic based techniques along with its variation have been used for authentication of CLO from oil adulterants. FTIR spectroscopy along with multivariate calibrations have been reported to be used for authentication of CLO from animal fats and vegetable oils fruitfully. Because of its capability to separate specific components in CLO, chromatographic techniques are suitable for such authentication using specific markers. Keywords: cod liver oil, physico-chemical properties, biological activity, authentication.